2014
DOI: 10.1186/1752-0509-8-s1-s1
|View full text |Cite
|
Sign up to set email alerts
|

Inferring transcription factor collaborations in gene regulatory networks

Abstract: BackgroundLiving cells are realized by complex gene expression programs that are moderated by regulatory proteins called transcription factors (TFs). The TFs control the differential expression of target genes in the context of transcriptional regulatory networks (TRNs), either individually or in groups. Deciphering the mechanisms of how the TFs control the expression of target genes is a challenging task, especially when multiple TFs collaboratively participate in the transcriptional regulation.ResultsWe mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Data integration is both a challenge and an opportunity and most certainly an increasing reality in genome research. Scientists have acknowledged that biological systems cannot be understood by the analysis of single-type datasets as the regulation of the system certainly occurs at many levels (see [ 29 , 44 ] and in this supplement [ 45 ]). Therefore projects have appeared aiming to investigate biological systems at several levels and create large heterogeneous data-sets .…”
Section: Introductionmentioning
confidence: 99%
“…Data integration is both a challenge and an opportunity and most certainly an increasing reality in genome research. Scientists have acknowledged that biological systems cannot be understood by the analysis of single-type datasets as the regulation of the system certainly occurs at many levels (see [ 29 , 44 ] and in this supplement [ 45 ]). Therefore projects have appeared aiming to investigate biological systems at several levels and create large heterogeneous data-sets .…”
Section: Introductionmentioning
confidence: 99%
“…The study by Mak et al (2014) demonstrated that apoptosis repressor with caspase recruitment domain (ARC), encoded by the NOL3 gene [MIM: 605235], is repeatedly overexpressed in diagnosed AML samples, and is involved in the regulation of apoptosis of cardiac cells. However, the precise molecular mechanism regulating this antiapoptotic protein still remains unknown due to the overwhelming number of possible combinations in high-throughput datasets (Awad and Chen 2014). Here, the PH-E dimension reduction method was applied to identify two-and three-way regulatory interactions controlling the variation of ARC/NOL3 (1 of the remaining 16,976 genes).…”
Section: Interaction Regulation Model For Arc/nol3mentioning
confidence: 99%
“…This implies that literature for the known three-way interactions is fairly sparse at the present time due to the small number of scalable methods; thus, all findings are likely to be novel (cf. Awad and Chen 2014).…”
mentioning
confidence: 99%
“…They interact with specific sites on genomic DNA, often recruiting other co-factors to the location, resulting in activation or repression of the corresponding genes. Analysis of cell signaling responses to stimuli is complicated by the fact that TFs generally control several genes, most genes are controlled by multiple TFs, and any given stimulus can result in the activation of multiple TFs [ 10 12 ]. Moreover, TF levels must change in response to a stimulus but, in most cases, must then return to baseline levels to avoid long-term perturbation of cellular function [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%